Literature review - Burt, C.; Caccetta, Louis (2018)
© 2018, Springer International Publishing AG. In this chapter, we present a detailed literature review of the equipment selection problem in surface mining as well as the closely related equipment selection problem in the construction industry. We review the modelling and solution methods that have emerged in both the mining and operations research literature. We also consider a number of closely related problems such as shovel-truck productivity, mining method selection, scheduling, dispatching and allocation problems. Our review considers a broad range of modelling and solution approaches that can or have been used for these related problems.